Alih wahana folklor Indonesia dalam tumbler kopi - Gunawan Wiradharma; Zul Fahmi; Melisa Arisanty (Universitas Bunda Mulia, 2022)
In the current era of digitalization, the development of folklore culture has changed drastically. Folklore, which was originally known as an oral tradition, was gradually eroded, destroyed, and transformed into something new. The purpose of this research is to find out how to transfer a folklore tradition into a Starbucks coffe tumbler. Qualitative followed by descriptive analysis method is the type of method used in this study indicate that the process of transferring the folklore tradition into the form a Starbucks coffe in the form of shrinking and varied changes. the shrinking of the transfer of oral folklore into a Starbucks coffe tumbler is very much dominated by the substructure of characters and plots. Meanwhile, in the form of non-verbal folklore, it displays the shape of the building, traditional clothes, and the technology used by the area. This research also shows that the transfer of folklore traditions into the form of a tumbler brings a crucial and big idea for cultural preservation and environmental care.